Modification of the Tumor Microenvironment Enhances Anti-PD-1 Immunotherapy in Metastatic Melanoma - Guilan Shi; Megan Scott; Cathryn G. Mangiamele; Richard Heller (MDPI AG, 2022)
Resistance to checkpoint-blockade treatments is a challenge in the clinic. Both primary and acquired resistance have become major obstacles, greatly limiting the long-lasting effects and wide application of blockade therapy. Many patients with metastatic melanoma eventually require further therapy. The absence of T-cell infiltration to the tumor site is a well-accepted contributor limiting immune checkpoint inhibitor efficacy. In this study, we combined intratumoral injection of plasmid IL-12 with electrotransfer and anti-PD-1 in metastatic B16F10 melanoma tumor model to increase tumor-infiltrating lymphocytes and improve therapeutic efficacy. We showed that effective anti-tumor responses required a subset of tumor-infiltrating CD8+ and CD4+ T cells. Additionally, the combination therapy induced higher MHC-I surface expression on tumor cells to hamper tumor cells escaping from immune recognition. Furthermore, we found that activating T cells by exposure to IL-12 resulted in tumors sensitized to anti-PD-1 treatment, suggesting a therapeutic strategy to improve responses to checkpoint blockade.